Asphalt Children and City Streets - Mesquita, Mônica. author. aut Link
XIV, 157 p.
Keywords: This work explores the urban experiences of street children in sao paulo, brazil through the mathematical epistemic regimes at the core of their survival strategies. We also draw attention to the situation of street children across time, space, culture, and history. Our goal is to recognize, understand, and validate forms of mathematics constructed and used outside of the established institutions of mathematical production. We base our analysis on "the mathematical imagination", which draws together social constructionism and ethnomathematics. Theoretically, we draw heavily on the durkheimian tradition in sociology and anthropology. We focus on a form of practice that links the formal and the informal in order to realize the full power of mathematical knowledge as a social thing (in durkheim's sense), a product of the collective consciousness that expresses collective realities and a category of knowledge present in every culture. This is as true for mathematics at the margins as it is for professional mathematics. Our work contributes to an emerging political manifesto of the marginal that demonstrates the social realities and social power of their mathematics. This book should be of interest to social scientists, students of mathematics and ethnomathematics, and everyone interested in the situation of marginalized children.